How to Re-Introduce Gray Partridges - Conclusions from a Releasing Project in Switzerland - Francis Buner (National Quail Symposium Proceedings, 2017)
Once a widespread farmland bird in Switzerland, the Gray Partridge (Perdix perdix) has declined drastically since the 1960’s as a result of agricultural intensification and changes in predator abundance. In 1991 the wild population had dropped to ≈ 17 pairs only. We initiated a reintroduction experiment of Gray Partridge to investigate its feasibility for conservation of the species in Switzerland. Between 1998 and 2001 we released 145 partridges in the Swiss Klettgau, an intensively cultivated area from which the species had become extinct in 1993, but had since been ecologically enhanced with wild-flower strips and hedges up to 5.8% of the available habitat in the release area (≈530ha). Although the duration of the study was too short to prove if further partridge re-introductions in Switzerland or abroad will be successful in terms of creating self-sustainable populations, it is possible to draw four basic conclusions for future partridge re-introduction projects: 1) prior to every partridge re-introduction or re-establishment the habitat must be enhanced with permanent habitat structures, 2) if translocated wild birds are not available for release, chicks should be fostered whenever possible to increase their survival, in the best case to wild birds still resident in the area, 3) reintroductions should only be envisaged in areas with low predator numbers and human activities, 4) in order to find possible weaknesses in re-introduction projects, post-release monitoring is essential to ensure the project targets are met.
Keywords: disturbance; gray partridge; habitat enhancement; habitat use; parent fostering; Perdix perdix; re-introduction; survival; Switzerland